Pengaruh AHH, AHLS Dan PDRB Terhadap Jumlah Penduduk Miskin Di Provinsi Aceh - Siti Khodijah Bancin; Umaruddin Usman (JURNAL EKONOMIKA INDONESIA, 2020)
This study aims to determine the effect of life expectancy, school lenght expectancy, and gross regional domestic product on the number of poor people in Aceh Province. The data used in this study is panel data from 2011 to 2017. The data analysis method used is panel data regression analysis.This study uses panel data from 2011 to 2017. The data analysis method used is the Panel data regression analysis. The results partially show that life expectancy has a negative and insignificant effect on the number of poor people in Aceh Province, school length expectancy has a positive but insignificant effect on the number of poor people in Aceh Province, and the Gross Regional Domestic Product has a negative and insignificant effect on the poor people in Aceh Province. Simultaneously, life expectancy, school length expectancy, and gross regional domestic product have a positive and significant effect on the number of poor people in Aceh Province..